1999
DOI: 10.1128/jvi.73.2.1689-1694.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Lck Binding Domain of Herpesvirus Saimiri Tip-484 Constitutively Activates Lck and STAT3 in T Cells

Abstract: Constitutive activation of signal transducers and activators of transcription (STATs) has been associated with oncogenesis. Previously, a protein required for T-cell transformation by the DNA tumor virus herpesvirus saimiri (HVS) strain 484, designated tyrosine kinase-interacting protein (Tip-484), was shown to interact with and dramatically upregulate the activity of the STATs in an Lck-dependent manner. The minimal region of Tip-484 responsible for binding Lck was defined as a 10-residue C-terminal Src-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Thus, dominant-negative Jaks are unable to inhibit either Stat5 activation or factor-independent cell proliferation induced by Bcr-Abl. 129 In addition, v-Src can directly activate Stat3, 130 whereas the Herpesvirus Tip protein co-associates Lck and Stat3, leading to constitutive Stat3 activation in T cells transformed by this virus, 131 suggesting that in these cases Jaks are also superfluous. In contrast, numerous recent studies have provided strong evidence for a role of Stats in the transformation process.…”
Section: Evidence For Jak-stat Involvementmentioning
confidence: 99%
“…Thus, dominant-negative Jaks are unable to inhibit either Stat5 activation or factor-independent cell proliferation induced by Bcr-Abl. 129 In addition, v-Src can directly activate Stat3, 130 whereas the Herpesvirus Tip protein co-associates Lck and Stat3, leading to constitutive Stat3 activation in T cells transformed by this virus, 131 suggesting that in these cases Jaks are also superfluous. In contrast, numerous recent studies have provided strong evidence for a role of Stats in the transformation process.…”
Section: Evidence For Jak-stat Involvementmentioning
confidence: 99%
“…Similarly, Tip-C484 markedly increases the in vitro phosphotransferase activity when Lck immuncomplexes from transiently transfected Jurkat T cells [84] or Lck-reconstituted JCaM1 cells [98] were used. The activating function could be mapped to the Lck binding site of Tip spanning the CSKH and the SH3B motifs [99]. A more detailed analysis revealed that both motifs are required to achieve Lck activation as mutation of either one resulted in a Tip protein that has no impact on the phosphotransferase activity of CD4-Lck immune complexes [97].…”
Section: R E G U L a T I O N O F L C K A C T I V I T Y B Y T I Pmentioning
confidence: 99%
“…STAT activation also correlates with the progression of diverse hematopoietic malignancies ( Table 2), such as various leukemias 24,28,37-42 and lymphomas. [42][43][44][45][46][47][48] In addition, Stat3 is frequently activated in both multiple myeloma cell lines and tumors derived from patient bone marrows. 49 Recently, the role of STAT signaling as it relates to the pathogenesis of multiple myeloma has been elucidated.…”
Section: Activation Of Stat Signaling In Human Cancermentioning
confidence: 99%